International Student-Athletes in Canadian Interuniversity Sport (CIS) - Karen Danylchuk; Dan Grbac (University of Kansas Libraries, 2016)
This exploratory study investigated the landscape of international student-athletes participating in Canadian Interuniversity Sport (CIS), the governing body for university sport in Canada, with respect to number, sport, and gender breakdown, as well as their perceptions, motivations, and experiences. Of the over 11,000 CIS student-athletes competing in 2012-14, 5.1% were international. In addition, the sports with the highest number of international student-athletes were basketball and soccer. Semistructured interviews with 16 international student-athletes from the four regional associations determined that the majority of participants were motivated to attend a Canadian university for the opportunity to combine athletics with academics. Furthermore, the experiences of those international student-athletes interviewed were mostly positive. This study may benefit university institutions, their athletics programs, as well as the CIS by providing knowledge of the motives of international student-athletes as well as ways to enrich the international student-athlete experience.